The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0167103
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Health of the Nation Outcome Scales (HoNOS) in Predicting Mental Health Service Costs for Patients with Common Mental Health Problems: Historical Cohort Study

Abstract: BackgroundFew countries have made much progress in implementing transparent and efficient systems for the allocation of mental health care resources. In England there are ongoing efforts by the National Health Service (NHS) to develop mental health ‘payment by results’ (PbR). The system depends on the ability of patient ‘clusters’ derived from the Health of the Nation Outcome Scales (HoNOS) to predict costs. We therefore investigated the associations of individual HoNOS items and the Total HoNOS score at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(64 reference statements)
0
9
0
4
Order By: Relevance
“…Large datasets have thus become available to evaluate the psychometric quality of the instrument, and some negative findings have emerged. For instance, the HoNOS appears not to be associated with need-for-care as operationalized by costs of treatment in a large British cohort of 1343 patients with common mental health problems [ 35 ]. For this patient group, the sensitivity to change in severity of psychopathology of the HoNOS appears to be limited as only three items (7, 8, and 9) seem relevant and appropriate [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large datasets have thus become available to evaluate the psychometric quality of the instrument, and some negative findings have emerged. For instance, the HoNOS appears not to be associated with need-for-care as operationalized by costs of treatment in a large British cohort of 1343 patients with common mental health problems [ 35 ]. For this patient group, the sensitivity to change in severity of psychopathology of the HoNOS appears to be limited as only three items (7, 8, and 9) seem relevant and appropriate [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…O grupo constrói, por meio de suas falas (linguagem), explicações inconscientes que justificam alguns obstáculos relacionados ao cuidado do idoso com transtorno mental (11) . intersetorial (20)(21) . Sendo assim, mais uma estratégia seria a partir das representações da equipe sobre a ausência de rede e protocolos, a construção de indicadores para avaliação dessas representações (1,10,20) .…”
Section: La Percepción De Los Profesionales De La Salud Sobre El Cuidunclassified
“…intersetorial (20)(21) . Sendo assim, mais uma estratégia seria a partir das representações da equipe sobre a ausência de rede e protocolos, a construção de indicadores para avaliação dessas representações (1,10,20) .…”
Section: La Percepción De Los Profesionales De La Salud Sobre El Cuidunclassified
See 1 more Smart Citation
“…More recently, however, HoNOS total score was found not to be a useful predictor of mental health service costs in a sample of patients with common mental health problems, and indeed only the 'self injury' item showed any relationship [18]. Golay and colleagues [19] also found that overall the HoNOS items had weak predictive validity for duration of stay in hospital, re-hospitalization and also time before re-hospitalization.…”
Section: Introductionmentioning
confidence: 97%